Hawaiian Futurism: Written in the Sky and Up Among the Stars. Issue 1 (2016) - Amos, Kelsey
Abstract : In this article I explore two novels, Written in the Sky and Up Among the Stars, by Matthew Kaopio, as instances of indigenous futurism from a Kanaka Maoli (Hawaiian) writer. Although Kaopio's work must be considered in relation to the body of Hawaiian literature, this article looks at insights that emerge from treating the novels as instances of indigenous futurism and reading with an eye for the ways that Kaopio constructs and imagines an Indigenous world by subverting settler–colonial expectations, drawing instead on Indigenous conceptions of reality, literacy, and history. I argue specifically that Kaopio connects Hawaiian ideas about ʻāina-based Indigenous literacy with an appropriation of the Mormon revelatory tradition in order to elaborate for readers a syncretic yet thoroughly Kanaka Maoli spiritual order and philosophical foundation for resurgence. Within this worldview, the figure of the Indian is reappropriated and claimed as ancestor to Native Hawaiians, serving not as what Jodi Byrd calls a "transit of empire" but rather as a transit of resurgence (10). The paper also attempts to perform what Chadwick Allen has called " purposeful Indigenous juxtapositions, " but from my own position as a settler–scholar (xviii). I juxtapose Kaopio's novels with both Little House on the Prairie by Laura Ingalls Wilder and the postcolonial sf of Vandana Singh in order to examine the authors' different treatments of the land, the space of the home, and homeless figures of abjection.